Implementation of Strategy in Multinational Corporations: An Exploration of Foreign Subsidiaries’ Perspective - Fatmi, Rehani (2014)
Implementation of strategy has always been more difficult than devising a good strategy. Implementation plans can be mired by a multitude of execution related problems which have been well researched and discussed in management literature. One of the problem arises from trade-offs between short-term revenue and profitability targets and long-term strategic goals that managers must balance. Strategists display a substantial amount of dissonance in deciding whether companies should stay committed to competing in a particular way or demonstrate flexibility to compete effectively in a variety of ways. In multinational companies such tensions can be exacerbated by the cultural, administrative, geographical and economic distance between the subsidiary that executes strategy and its headquarters which formulates the corporate strategy. This interpretive exploratory research based on the views and opinions of managers of subsidiaries belonging to multinational companies, highlighted a number of issues currently being faced at the subsidiary level. Two broad areas of improvement have been derived from those interviews – one relating to organizational design and the other to strategic human resource management.